A Study Assessing The Impact Of Academic Detailing Program On Childhood Diarrhoeamanagement Among The Primary Healthcare Providers In Banke Region, Nepal - Khanal, Saval (2010)
Childhood diarrhoea is common in Nepal. Studies had reported poor knowledge and irrational prescribing practice among healthcare professionals for childhood diarrhoea management. Academic detailing had been used to promote rational prescribing in many developed countries, but uncommon in developing countries like Nepal. With this background, a prospective interventional study was conducted in Banke district of Nepal to evaluate the impact of academic detailing on childhood diarrhoea and its management to the randomly divided 235 primary healthcare providers. Data on knowledge, attitude and practice were collected with the help of validated semistructured questionnaire; and data on prescribing pattern was collected with the help of simulated clients. At baseline, Knowledge (K) score, Attitude (A) score, Practice (P) score and Total KAP score for the participants in control group were 7, 38, 26 and 71, respectively which was not significantly different than the participants of intervention group. K-score, A-score, P-score and KAP-score for the participants in intervention group were 7, 37, 25 and 70, respectively. However, it improved significantly in participants of intervention group during first and second follow up phases of the study.